A new species of genus Pseudachorutes Tullberg, 1871 (Collembola: Neanuridae:Pseudachorutinae) from China - Gao, Yan; Palacios-Vargas, José G. (Zootaxa, 2008)
A new species of Pseudachorutes, P. polychaetosus sp. nov., from Lishan Mountain, Shaanxi Province, Northwest China, is described and illustrated. It is distinct from other species in being polychaetotic in having both macrosetae and microsetae well differentiated and in strong hypertrichosis. Males of the new species are sexually dimorphic, a character not known before in the genus.